Doxycycline improves tendon and cartilage pathologies in preclinical studies: current concepts. Issue 3 (17th May 2020) - Dean, Robert S; Kahat, David H; Graden, Nathan R; DePhillipo, Nicholas N; LaPrade, Robert F
Abstract : Matrix metalloproteinases (MMPs) are enzymes that are elevated during states of inflammation and have specifically been linked to cartilage, tendon and bone pathologies. Concentrations of these enzymes fluctuate naturally with various injury states, and these enzymes have been shown to be directly inhibited by doxycycline. Historically, doxycycline has been used exclusively for its antimicrobial properties, but recent studies have investigated the anti-inflammatory properties of doxycycline and its effects on musculoskeletal pathologies. This study sought to describe the current use of doxycycline for its MMP inhibitory properties in the setting of musculoskeletal pathologies. During preclinical studies, improved healing properties were noted acutely in tendon injuries following surgical repair and chronically in cartilage injuries, demonstrating decreased rates of joint space narrowing and improved cartilage quality. There is only one known clinical trial that has examined doxycycline use, and it reported that doxycycline can decrease the rate of joint space narrowing in patients with osteoarthritis. Furthermore, doxycycline was well tolerated with minimal side effects reported in both animal and human studies. While it can be reasonably inferred that the positive effects of doxycycline are related to its ability to inhibit MMP activity, further clinical research is warranted to investigate the use of doxycycline in orthopaedic and musculoskeletal pathologies. Level of Evidence: Current Concepts, Level IV.